통합돌봄센터 계획을 위한 고령인구의종합사회복지관 이용실태 연구- 경기도 남부 4개 사회복지관을 대상으로 - 한은비; 장진샹; 권순정 (의료·복지 건축, 2020)
Purpose: The purpose of this study is to derive basic data for desirable location and functions of the integratedcare center. Methods: Survey, Questionaire and statistical analysis are the main research methodof this study. In order to collect data related to utilization pattern and favorite functions of the seniorpeople, researchers have visited 4 social welfare facilities located in Southern Gyeonggi Province. 403questionaires have been gathered from 4 facilities and they have been analyzed by using Excel Programof MS. Results: First, compared to other services, healthcare services have been preferred by many olderpeople in Social welfare Facilities. This means that integrated care centers providing healthcare servicesfor older people rather than services for children or disabilities is desirable. Second, Integrated CareCenters had better be established within the walk distance of elderly people. If it is not easy, the introductionof shuttle bus for older people is desirable. Especially, in case of large Care Center. Implications: This study shows that small facility with community care rather than big facility is desirablefor small community in the point of friendliness, convenience, economy, etc.. However it is necessary tocombine welfare service and healthcare service even in small centers.
Keywords: 통합돌봄센터; 종합사회복지관; 돌봄서비스; 고령인구; Integrated Care Center; Integrated Social Welfare Facilities; Care Service; Elderly Population